Microleakage Difference of Self-Adhering Flowable Composite and Flowable Composite After Sitric Acid Immersion - Widya saraswati; Adioro Soetojo; Veda Sahasika Azaria Nariswari; Annisa Salsabila Andika Putri; Sekar Firdhea Rizkifa Soetanto (Universitas Airlangga, 2021)
Background: Flowable composite (FC) is a composite that has low viscosity so that it can flow to the cavity. Selfadhering flowable composite (SAC) is a type of flowable composite which is applied without the stages of etching and bonding because it has an acid monomer. Degradation in the oral cavity such as exposure to acidic fluid and changes in temperature can result in microleakage between the restoration and the cavity wall which can cause secondary caries, and hypersensitivity. Purpose: To prove the difference of microleakage between self-adhering flowable composite (SAC) and flowable composite (FC) after immersed in citric acid. Methods: 28 bovine incisors were cleaned and soaked with 0.01% thymol then divided randomly into 4 groups, groups 1 and 2 are immersed in citric acid with SAC restoration and FC restoration. Groups 3 and 4 are SAC and FC material control groups. All groups were prepared class V with cylindrical shapes. Groups 1 and 2 were treated with thermocycling from 5o and 55o C for 120 cycles and immersed in 3364 ppm citric acid for 24 hours. All groups were immersed in 2% methylene blue for 24 hours, then buccolingual cut for 1 mm. Evaluation of microleakage was seen by the amount of color that entered between the restoration wall and the cavity using a 40x magnification Digital Microscope. Test data analysis using the Kruskal Wallis and Mann Whitney U. Results: Significant differences were found between SAC and FC. Significant differences were also obtained from SAC compared with the SAC control group. Whereas in the comparison between FC and FC control group no differences were found. Conclusion: Microleakage SAC is bigger than FC and SAC control group, but FC has no difference with FC control group.